Learning Path: Expert Python Projects - Curator, Taabish (Packt Publishing, 2017)
Unlock the power of Python with expert-level projects In Detail Python is one of the most powerful, flexible, and popular programming languages in the world. Become an expert with a plethora of projects with this Learning Path. This Learning Path follows a project-based approach to help you learn all the advanced concepts of Python. We will focus on GUI projects with Tkinter, look at data visualization in deep, and then move on to machine learning. This Learning Path aims to get you well-versed with every concept of Python by teaching a broad range of topics. This Learning Path aims to equip you with a mastery of Python like no other! Prerequisites : Requires beginner-level knowledge of Python and cursory information about Tkinter, data visualization, and machine learning. Resources : Code downloads and errata: Mastering Python - Second Edition Tkinter GUI Application Development Projects Python Data Visualization Solutions Python Machine Learning Solutions PATH PRODUCTS This path navigates across the following products (in sequential order): Mastering Python - Second Edition (5h 21m) Tkinter GUI Application Development Projects (4h 51m) Python Data Visualization Solutions (3h 27m) Python Machine Learning Solutions (4h 27m).